KOMPETENSI GURU - Madani, Ahmad (Jurnal An-Nahdhah, 2014)
Education, in general, is defined as a process of transferring values from adults (teachers or parents) to children to become adults. In transfering knowledge to students, a skill as a teacher is required. Without this skill , the interaction process of teaching could not run condusively. Hence, competence in the sense of abilty is absolutely necessary for teachers in conducting their task as educator.A teacher must have four competencies, namely pedagogical competence, personal competence, social competence, and professional competence. Pedagogical competence is defined as teachersâ ability to manage learning. Indicators for this competence are lesson plan, implementation of learning, assessment of learning outcomes. Personal competence is related to a solid personality, mature personality, wise personality, authoritative personality, and noble personality that can be a role model for the students. Social competence includes relationships with the peers, relationships with the students, relationships with the parents, and relationships with the surroundings. Professional competence is defined as ability in mastering the substance, in mastering teaching methodologies, in mastering evaluation techniques as well as understanding, appreciating, and practicing moral values and code of professional conduct.In the context of Islamic education, educators are people who are responsible for the development of students by giving several efforts in developing the potencies of the students, both affective (flavors), cognitive (copyright) and psychomotor (intention). Competencies required for a good teacher in Islam is piety to Allah, knowledgeable, healthy, and noble.